2015
DOI: 10.1007/s00431-015-2676-4
|View full text |Cite
|
Sign up to set email alerts
|

Catch-up growth in term and preterm infants after surgical closure of ventricular septal defect in the first year of life

Abstract: • Growth impairment in infants with unrestrictive ventricular septal defects is well documented in literature. • Surgical correction in the first months of life is the current option for most ventricular septal defects, leading to a more favourable growth pattern. • Rapid growth during infancy may be associated with the development of insulin resistance, metabolic syndrome, obesity and cardiovascular disease later in life. What is New: • Literature is inconsistent about catch-up growth velocities after ventric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…Previously, several studies found that CHD patients could catch-up growth significantly after corrective cardiac surgery in both cyanotic and acyanotic CHD (Carmona et al, 2012; Cheung et al, 2003; Li et al, 2019). Martins et al, demonstrated that early VSD closure resulted in significant acceleration of post-operative growth within 3–6 months in both term and preterm infants (Correia Martins et al, 2016). Regarding to Ratanachu-ek et al (Ratanachu-Ek and Pongdara, 2011) the WHZ of CHD patients increased after cardiac surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, several studies found that CHD patients could catch-up growth significantly after corrective cardiac surgery in both cyanotic and acyanotic CHD (Carmona et al, 2012; Cheung et al, 2003; Li et al, 2019). Martins et al, demonstrated that early VSD closure resulted in significant acceleration of post-operative growth within 3–6 months in both term and preterm infants (Correia Martins et al, 2016). Regarding to Ratanachu-ek et al (Ratanachu-Ek and Pongdara, 2011) the WHZ of CHD patients increased after cardiac surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, nutrient deprivation during the neonatal period is seen not only in preterm infants, but also in term infants requiring surgery and/or intensive care. Correia Martins et al reported that earlier surgical closure of ventricular septal defects resulted in better acceleration of postoperative growth than later surgery [21]. However, there has been scarce evidence on catch-up growth in term infants who underwent other types of surgeries.…”
Section: Discussionmentioning
confidence: 99%
“…Persistent malnutrition has been widely described in infants with CHD including in cardiac centres in other countries 9 11 , 14 , 70 73 We aimed to ensure that the principles of nutritional care within the pathway were as generic as possible to allow local adaptation within a variety of healthcare settings both nationally and internationally.…”
Section: Discussionmentioning
confidence: 99%